Assessment of Thermal Regulation before Urban Tree Cover Restoration in Verona, Italy (Epidemiology, Biostatistics, and Public Health, 2025)
BackgroundGreen spaces offer various essential regulating ecosystem services, with trees playing a significant role in mitigating urban heat island effects. In the éVRgreen project, we evaluated the potential of greenness to reduce air temperatures in Verona, Northern Italy, to serve as a baseline assessment before implementing an intervention of tree-cover restoration.MethodsIn the municipality area, we assessed blue/green cover (water, grass/agriculture, trees) and grey cover (bare soil, impervious surfaces) at >200,000 random locations (points) using i-Tree Canopy software. We installed 50 stations that monitored temperatures 2.5 m above ground. We estimated the percentage of blue/green spaces in 200-m radial buffers around each station by determining the proportion of sampled locations in the corresponding land cover classes. We retrieved data of land surface temperatures (LST) from the Landsat 8 satellite and spatially associated it with the sampled locations. We analysed whether land cover can mitigate summer LST (16 July 2024) and winter air temperatures (January 2025).ResultsOn 16 July 2024, the median (1st-3rd quartiles) LST was 37 (35-40) degrees Celsius in 61,335 locations covered by trees and 45 (43-47) degrees Celsius in 44,458 locations covered by impervious surfaces (p